Vegetarian, pescatarian and flexitarian diets: sociodemographic determinants and association with cardiovascular risk factors in a Swiss urban population. Issue 8 (28th October 2020) - Wozniak, Hannah; Larpin, Christophe; de Mestral, Carlos; Guessous, Idris; Reny, Jean-Luc; Stringhini, Silvia
Abstract: Prevalence and trends of different vegetarian diets remain unknown, with estimates varying depending on the source. Evidence suggests that vegetarian diets are associated with a more favourable cardiovascular risk profile. The present study aimed to assess the prevalence and trends of different types of vegetarian diets in a population-based representative sample, sociodemographic characteristics of participants following such diets and the association of these diets with cardiovascular risk factors. Using repeated cross-sectional population-based surveys conducted in Geneva, Switzerland, 10 797 individuals participated in the study between 2005 and 2017. Participants were classified as vegetarians, pescatarians, flexitarians or omnivores using an FFQ. Sociodemographic and cardiovascular risk factors were evaluated through questionnaires, anthropometric measurements and blood tests. Findings show prevalence of vegetarians increased from 0·5 to 1·2 %, pescatarians from 0·3 to 1·1 % and flexitarians remained stable at 15·6 % of the population over the study period. Compared with omnivores, vegetarians were more likely to be young (OR 2·38; 95 % CI 1·01, 5·6), have higher education (OR 1·59; 95 % CI 1·01, 2·49) and lower income (OR 1·83; 95 % CI 1·04, 3·21); pescatarians and flexitarians were more likely to be women (pescatarian: OR 1·81; 95 % CI 1·10, 3·00; vegetarian: OR 1·57; 95 % CI 1·41, 1·75) and flexitarians were also more likely to have a lower income (OR 1·31; 95 % CI 1·13, 1·53). Participants who adhered to any diet excluding/reducing meat intake had lower BMI, total cholesterol and hypertension compared with omnivores. The present study shows an increase in the prevalence of vegetarians over a 13-year period and suggests that the different vegetarian diets assessed are associated with a better cardiovascular risk profile.